The Autophagy Machinery Contributes to E-cadherin Turnover in Breast Cancer - Damiano, Valentina; Spessotto, Paola; Vanin, Giulia; Perin, Tiziana; Maestro, Roberta; Santarosa, Manuela (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is an intracellular catabolic process that is increasingly being recognized as a crucial factor in several human diseases including cancers. Mounting evidence suggests that autophagy allows tumor cells to overcome otherwise fatal stresses and to increase dissemination. Nevertheless, how autophagy controls these processes and in particular how it impinges on cell-cell adhesion is still poorly understood. Here, we investigate the role of autophagy in the turnover of the epithelial adhesion molecule E-cadherin in the context of breast cancer. We demonstrated in breast cancer cell lines that autophagy impinges on E-cadherin expression and in the configuration of adherens junctions. Besides, we showed that E-cadherin colocalizes with LC3B and SQSTM1/p62, two components of the autophagosome machinery. Pull down and immunoprecipitation analyses provided evidence that E-cadherin and SQSTM1/p62 physically interact. Moreover, the physical closeness of E-cadherin and SQSTM1/p62 was demonstrated by proximity ligation assays in breast cancer cell lines and primary tumors. Finally, we proved that the silencing of SQSTM1/p62 diminished the E-cadherin/LC3B colocalization, further supporting the role of SQSTM1/p62 in E-cadherin delivery to autophagosomes. These findings suggest that the activation of autophagy, reported in breast cancers with poor prognosis and in dormant breast cancer cells, may contribute to the control of tumor progression via downmodulation of E-cadherin protein levels.